Character The Author and Characters of a Work of Art as Interacting Linguistic Personalities - Ullieva Sanobar Khaydarovna (Periodica Journal, 2023)
Whatever text is created, the image of the author - its creator - determines all the elements of the structure (theme, idea, composition, selection and organization of language tools, etc.). Many domestic and foreign linguists, philologists, literary critics dealt with the problem of studying the linguistic personality of the author. Consider the main provisions of some of the presented theories. The author's subjectivity organizes the work and generates its artistic integrity. It constitutes an integral, universal, most important facet of art (along with its proper aesthetic and cognitive principles). The "spirit of authorship" is not only present, but dominates in any form of artistic activity: both if the work has an individual creator, and in situations of group, collective creativity, and in cases where the author is named, and when his name is hidden (anonymity, pseudonym, hoax)
Keywords: individualization; speech expression; selection